2023
DOI: 10.3390/cancers15051596
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Machine Learning in Palliative Care: A Systematic Review

Abstract: Objective: To summarize the available literature on using machine learning (ML) for palliative care practice as well as research and to assess the adherence of the published studies to the most important ML best practices. Methods: The MEDLINE database was searched for the use of ML in palliative care practice or research, and the records were screened according to PRISMA guidelines. Results: In total, 22 publications using machine learning for mortality prediction (n = 15), data annotation (n = 5), predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our study aligns with these findings, indicating that machine learning models may offer superior prognostic capabilities in oncology compared with traditional statistical methods, which are not as precise at predicting cancer prognosis. In the latest systematic review of ML in palliative care [ 48 ], Vu et al concluded that although ML in palliative care is often used to predict mortality, it is not restricted only to this purpose, as the recent literature in this domain shows the potentials of ML for other innovative use cases, e.g., for data annotation and predicting complications, as well. The authors also emphasized the need for more rigorous testing of the models to ensure their applicability in different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…Our study aligns with these findings, indicating that machine learning models may offer superior prognostic capabilities in oncology compared with traditional statistical methods, which are not as precise at predicting cancer prognosis. In the latest systematic review of ML in palliative care [ 48 ], Vu et al concluded that although ML in palliative care is often used to predict mortality, it is not restricted only to this purpose, as the recent literature in this domain shows the potentials of ML for other innovative use cases, e.g., for data annotation and predicting complications, as well. The authors also emphasized the need for more rigorous testing of the models to ensure their applicability in different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…For example, consider a risk prediction model being used to direct palliative care interventions. It is easier to train an ML-based tool to predict mortality, as a surrogate for palliative care needs, because mortality is less susceptible to measurement error and is available in palliative care medical records [ 58 , 59 ]. However, training an algorithm on mortality may not identify the individuals with high symptomatic or psychosocial needs who would benefit from palliative care the most.…”
Section: What Are the Factors To Consider In Using ML For Implementat...mentioning
confidence: 99%
“…Chatbots should be designed to deliver information in a manner that is easily understandable to patients, using plain language and minimizing the use of medical jargon [ 57 ]. Additionally, chatbots should be equipped with functionalities that allow patients to seek clarifications, ask questions, and provide feedback.…”
Section: Ethical Considerations In the Utilization Of Chatbotsmentioning
confidence: 99%